Imarah Al-Masajid dalam Al-Qur’an: Perspektif Marwan Bin Musa Dalam Kitab Hidayatul Insan Bi Tafsir Al-Qur’an - Diki Saputra Siregar; Amroeni Drajat (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2025)
This study examines the concept of ‘imārat al-masājid (the prosperity and development of mosques) in the Qur’an from the perspective of Abu Yahya Marwan bin Musa through his exegesis Hidāyatul Insān bi Tafsīr al-Qur’an. The focus of the study is directed toward the analysis of key verses, namely Q.S. At-Taubah: 18, Al-Baqarah: 114, and Al-Jinn: 18, which are then elaborated with the views of authoritative exegetes such as Ibn Kathir, Al-Maraghi, and Quraish Shihab. The method applied is thematic interpretation (tafsīr maudhū‘ī) with a descriptive-analytical approach. The findings reveal that the concept of mosque prosperity encompasses spiritual, social, educational, economic, and political dimensions. The mosque is not merely a place of worship but also serves as a center of community, education, social justice, social advocacy, and reconciliation. Marwan bin Musa’s interpretation emphasizes that mosque prosperity is a reflection of true faith, measured through devotion to prayer, zakat, and sincere worship of Allah. The novelty of this research lies in its systematic effort to uncover the thematic dimension of Marwan bin Musa’s exegesis on mosques, which has rarely been examined academically. This study discovers a new aspect in his interpretation that has not been significantly highlighted by other exegetes, namely the emphasis on the mosque as a transformative institution that actively contributes to empowering the Muslim community in both spiritual and social spheres. This finding aligns with contemporary realities that demand the mosque to function as a dynamic, inclusive, and relevant institution for modern Islamic civilization. Therefore, mosque prosperity should be understood as a collective responsibility grounded in monotheism (tawhid) and social ethics for the benefit of the ummah.